2014
DOI: 10.1371/journal.pone.0110856
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Utilization of Saccharum spp. Genetic Resources through Genetic Diversity Analysis and Core Collection Construction

Abstract: Sugarcane (Saccharum spp.) and other members of Saccharum spp. are attractive biofuel feedstocks. One of the two World Collections of Sugarcane and Related Grasses (WCSRG) is in Miami, FL. This WCSRG has 1002 accessions, presumably with valuable alleles for biomass, other important agronomic traits, and stress resistance. However, the WCSRG has not been fully exploited by breeders due to its lack of characterization and unmanageable population. In order to optimize the use of this genetic resource, we aim to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 66 publications
7
57
4
Order By: Relevance
“…In the present study, seven gSSR and eight EST-SSR primer pairs were used to prime the amplification of 205 polymorphic alleles from the leaf DNA samples of 181 sugarcane clones, with a mean of 13 polymorphic alleles per prime pair. This number was higher than the number reported by Nayak et al (2014) but lower than the number reported by Zheng (2009) andHuang (2009). On the other hand, the PIC values ranged from 0.79 to 0.99 for gSSRs and 0.78 to 0.99 for EST-SSRs.…”
Section: Efficacy Of Gssr and Est-ssrcontrasting
confidence: 68%
See 2 more Smart Citations
“…In the present study, seven gSSR and eight EST-SSR primer pairs were used to prime the amplification of 205 polymorphic alleles from the leaf DNA samples of 181 sugarcane clones, with a mean of 13 polymorphic alleles per prime pair. This number was higher than the number reported by Nayak et al (2014) but lower than the number reported by Zheng (2009) andHuang (2009). On the other hand, the PIC values ranged from 0.79 to 0.99 for gSSRs and 0.78 to 0.99 for EST-SSRs.…”
Section: Efficacy Of Gssr and Est-ssrcontrasting
confidence: 68%
“…However, phenotypic traits usually do not reflect the true level of diversity among sugarcane germplasm due to severe influence by environmental factors (Creste et al 2010;Singh et al 2010). To obtain reliable data to distinguish the genetic diversity among breeding lines in programs, DNA markers have also been used, including AFLP (amplified fragment length polymorphism) (Aitken et al 2006;Besse et al 1998), RFLP (restriction fragment length polymorphism) (Creste et al 2010), RAPD (random amplification polymorphism DNA) (Da Nawaz et al 2010;Ramakrishnan et al 2015), SRAP (sequence-related amplified polymorphism) (Alwala et al 2008;Chang et al 2012), SCoT (start codon targeted) (Que et al 2014), SSR (simple sequence repeat) Andru et al 2011;Cai et al 2005;Nayak et al 2014;Xu et al 1999;Zawedde et al 2014), ISSR (inter simple sequence repeat) (Alves de Almeida et al 2009;Devarumath et al 2012), and EST (expressed sequences tags)-SSR Singh et al 2013). Among these markers, SSR markers are highly informative, simple to use with reliable results (Senior et al 1998;Smith et al 1997), and have been widely applied to sugarcane Pan 2010;Pan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…officinarum (2 n = 80, x = 10) and S . spontaneum (2 n = 40–128, x = 8) (Irvine, ; Nayak et al ., ). The domesticated species S. officinarum is the major genome contributor to modern sugarcane cultivars (D'Hont, ), and widely cultivated for its ability to accumulate sucrose but vulnerable to several diseases.…”
Section: Introductionmentioning
confidence: 97%
“…One WCSRG is maintained in Coimbatore, India, and the other in Miami, Florida, in the United States (Alexander & Viswanathan, ; Comstock, Schnellt, & Miller, ). The WCSRG contains significant genetic diversity and valuable alleles for numerous morphological traits, sucrose, biomass yield, resistance to biotic and abiotic stresses and other quality traits (Nayak et al., ).…”
Section: Introductionmentioning
confidence: 99%